AI-assisted treatment planning for dental implant placement: Clinical vs AI-generated plans - Sukanta K Satapathy; Aishwarya Kunam; Rashme Rashme; Pooja Priyadarshini Sudarsanam; Anuj Gupta; H S Kiran Kumar (Wolters Kluwer Medknow Publications, 2024)
Background: Dental implant placement is a critical procedure in modern dentistry, requiring precise treatment planning to ensure successful outcomes. Traditionally, treatment planning has relied on the expertise of clinicians, but recent advancements in artificial intelligence (AI) have opened up the possibility of AI-assisted treatment planning. Materials and Methods: Twenty patients requiring dental implant placement were included in this comparative study. For each patient, a clinical treatment plan was created by an experienced dentist, while an AI algorithm, trained on a dataset of implant placement cases, generated an alternative plan. Various parameters, including implant position, angulation, and depth, were compared between the two plans. Surgical templates were fabricated based on both plans to guide implant placement accurately. Results: The results of this study indicate that AI-generated treatment plans closely align with clinical plans in terms of implant positioning, angulation, and depth. Mean discrepancies of less than 1 mm and 2 degrees were observed for implant position and angulation, respectively, between the two planning methods. The AI-generated plans also showed a reduction in planning time, averaging 10 min compared to the clinical planning, which averaged 30 min per case. Additionally, the surgical templates based on AI-generated plans exhibited similar accuracy in implant placement as those based on clinical plans. Conclusion: AI-assisted treatment planning for dental implant placement demonstrates promising results in terms of accuracy and efficiency.